Use of a continuously recording intravascular oxygen electrode in the newborn. Issue 11 (November 1974) - Goddard, P.; Keith, I.; Marcovitch, H.; Roberton, N. R. C.; Rolfe, P.; Scopes, J. W.
Abstract : The use of a continuously recording intravascular Po2 electrode is described. The electrode, based on the Galvanic principle, is built into the tip of a French gauge (FG) 5 umbilical arterial catheter. Its use has considerably improved the management of oxygen therapy in the seriously ill premature newborn infant and has done so with at least a 50% reduction in the amount of blood needed to be removed for gas analysis.